2022
DOI: 10.3389/fnut.2022.922993
|View full text |Cite
|
Sign up to set email alerts
|

A multi-strain probiotic blend reshaped obesity-related gut dysbiosis and improved lipid metabolism in obese children

Abstract: Background and aimsObese children are more prone to becoming obese adults, and excess adiposity consequently increases the risk of many complications, such as metabolic syndromes, non-alcoholic fatty liver disease, cardiovascular disease, etc. This study aimed to evaluate the effects of multi-strain probiotics on the gut microbiota and weight control in obese children.MethodsA double-blind, randomized, placebo-controlled trial was carried out on overweight and obese children. Subjects received 12 weeks of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Interestingly, probiotic/prebiotic applications performed in human clinical and animal models effectively enhanced the abundance of probiotics in the intestines and significantly reduced TMA and TMAO metabolism, accompanied by other benefits such as decreased body weight, lipids, and cholesterol marker levels [ 52 , 54 , 55 ]. Probiotic supplementation alone completes the regulation of the gut microbiota, with improved lipid profiles and reduced inflammation [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, probiotic/prebiotic applications performed in human clinical and animal models effectively enhanced the abundance of probiotics in the intestines and significantly reduced TMA and TMAO metabolism, accompanied by other benefits such as decreased body weight, lipids, and cholesterol marker levels [ 52 , 54 , 55 ]. Probiotic supplementation alone completes the regulation of the gut microbiota, with improved lipid profiles and reduced inflammation [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, from a metaanalysis of 13 trials (818 T2D participants), Liang et al 114 highlight their safety profile in children and pregnant women. [115][116][117] Cardiovascular disease (CVD) affects one in three and kills one in two T2D patients. 118 CVD accounts for 20%-49% of the total cost of treating a T2D patient with comorbid cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota can influence the efficiency of energy acquisition from digested nutrients and fat storage in the body. By transferring fecal microbiota transplantation to the host or feeding probiotics, obesity phenotype indicators can be improved, and the levels of HDL-C, LDL-C, adiponectin, leptin, and TNF-α can be regulated ( 116 , 119 121 ). Animal experiments have also found that obese mice receiving microbiota from post-bariatric surgery mice showed enrichment of mucin-degrading Akkermansia muciniphila or Bacteroides fragilis , increased levels of tryptophan-derived metabolites, SCFAs, and acylcarnitines, increased brown fat mass and activity, increased energy expenditure, and improved immune homeostasis in white adipose tissue ( 122 ).…”
Section: Dysbiosis Of the Gut Microbiota Can Lead To Metabolic Disordersmentioning
confidence: 99%